Efeito da variabilidade regional do substrato dentinário e modo de aplicação de sistemas adesivos nas propriedades mecânicas da camada adesiva - Mendes, Yasmine Bitencourt Emilio (2010)
The aim of this study was to assess the effect of different modes of application of a conventional adhesive system AdperTM Single Bond [SB] and of two self-etch adhesives AdperTM SE Plus [SE] and AdheSE® [AD] and influence of dentin depth on mechanical properties of hardness and elastic modulus of adhesive layer using the nanoindentation technique. The surfaces occlusal of 48 caries-free human third molars were removed and the smear layer standardized for the obtaining of a flat superficial dentin surface, in two levels: superficial dentine (DS) or deep dentine (DP). The adhesives were applied on the dentin surface in two layers, under active (AA) or passive (PA) application and photoactivated (10 s / 500 mW/cm2). After composite build-ups were constructed incrementally and were stored in water by 24 h. The teeth were sectioned in perpendicular direction to obtain specimens in form of bonded sticks with a cross-sectional area of 0.8 ± 0.1mm2, separating the central bonded sticks of each tooth for they be fastened in sample holder and metallographic polishing. The test of nanoindentation was made on composite resin, adhesive system and dentin regions. The results of hardness and elastic modulus (GPa) of adhesive layer were analyzed by a three-way ANOVA and Tukey’s multiple comparison tests (α=0.05) and also took place the two-way ANOVA for each adhesive separately. The mean and standard deviation of hardness and elastic modulus values of composite resin (GPa) were respectively (0.94 ± 0.05) and (13.41 ± 0.52). In dentin, the hardness was (0.89 ± 0.06) and the elastic modulus (17.51 ± 0.71). In the adhesive layer, the highest hardness (0.32 ± 0.02) and elastic modulus (5.54 ± 0.47) of SB were obtained in DS group. The elastic modulus in the adhesive layer of SE (4.11 ± 0.10) was lowest in AA group. For the adhesive layer of AD, just the mode of application was statistically significant (p=0.0041), being AA (0.29 ± 0.01) larger than PA (0.26 ± 0.01) (p=0.0042). It was concluded that: 1) passive application in superficial dentine got greaters values of hardness and modulus of elasticity of the SB and of SE, 2) the active application in deep dentine resulted in bigger values of the properties in study of SB, 3) active application significantly influenced the values of hardness in the area of the adhesive layer of the AD ones in such a way in superficial dentine how much in deep, but didn’t influence the modulus.